Utilization of the Winkler scale of plants using big data temperature presented by the Korea Meteorological Administration - Park, Jae-Ryoung; Kim, Eun-Gyeong; Jang, Yoon-Hee; Kim, Kyung-Min (Frontiers in Plant Science, 2024)
Rice is an important food source responsible for calories for most people around the world.However, due to the recent rapid temperature rise, we are facing social issues related to the increase in winkler scale. In this study, a strategy for screening potential candidate genes related to the yield according to winkler scale presented, and the possibility of using candidate gene identified through sequence haplotype and homology analysis as a breeding source suggested. QTL for Winkler scale was identified using 120 double haploid populations derived from a cross between Cheongchoneg, Indica, and Nagdong, Japonica. 79 candidate genes were detected in the identified QTL region, and OsHAq8 was finally screened.Potential candidate genes that can affect yield due to temperature rise screened and classified according to function. Through haplotype analysis, OsHAq8 derived from the indica group and orthologous to Graminae's activator of Hsp90 ATPase, suggesting that it is a candidate gene involved in yield according to temperature during the growing period. The expression level of OsHAq8 increased as winkler sclare increased. The findings of this study can serve as a crucial indicator for predicting harvest time and grain quality while achieving a stable yield through marker selection and adaptation to climate change. Climate change occurs more frequently. In these situations, it is very important to predict harvest time and apply relevant candidate genes to breeding.The candidate genes presented in this study can effectively applied to rice breeding in preparation for climate change.